Autophagy and vacuolar biogenesis during the nectary development - Machado, Silvia R. [UNESP]; Rodrigues, Tatiane M. [UNESP] (Springer Nature, 2019)
Main conclusion: Different autophagy pathways are a driver of vacuolar biogenesis and are development stage specific during the extrafloral nectary development in Citharexylum myrianthum. Abstract: Plant autophagy plays an important role in various developmental processes such as seed germination, pollen maturation and leaf senescence. However, studies that address the evidence of autophagy and its role in the development of plant glands are scarce and largely restricted to laticifers. Regarding nectary, studies have repeatedly pointed to signs of degradation associated with the end of the secretory cycle, without exploring autophagy. Likewise, the relationship between autophagy and biogenesis of vacuoles remains an unexplored issue. In this study, using conventional and microwave fixation in association with ultracytochemical methods for transmission electron microscopy, we investigated the occurrence of autophagy and its implication in the differentiation of extrafloral nectary in Citharexylum myrianthum (Verbenaceae) under natural conditions, focusing on the vacuole biogenesis. We described a variety of vacuole types associated with the stage of nectary epidermis development, which differs with respect to origin, function and nature of the products to be stored. Three distinct autophagy pathways were detected: macroautophagy, microautophagy (both restricted to the undifferentiated epidermal cells, at the presecretory stage) and megaautophagy (circumscribed to the differentiated epidermal cells, at the postsecretory stage). Our study clearly demonstrated that the vacuole variety and autophagy processes in the nectary epidermal cells are development specific. This study highlights the role of autophagy in vacuole biogenesis and its implications for the development of nectary and opens new venues for future studies on regulation mechanisms for autophagy in plant secretory structures under normal conditions.
Keywords: Macroautophagy; Megaautophagy; Microautophagy; Nectar secretory cells